PENGARUH KEPEMIMPINAN, PENGETAHUAN, KETERAMPILAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN BOJONEGORO - jurnalmap map; Maspriyadi ÔÇì; Mei Indrawati; Hidayat ÔÇì (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2019)
ABSTRACT This study aims to determine the effect of leadership, knowledge, skills and work motivation on the performance of employees of the Regional Development Planning Agency (Bappeda) of Bojonegoro Regency. This research is quantitative research, validity and reliability tests were carried out on 37 respondents from 49 population employees of the Bappeda in Bojonegoro Regency. The analysis technique used is multiple regression analysis carried out by t test and f test. The results showed that leadership, knowledge, skills, motivation simultaneously influenced the performance of Bojonegoro District Bappeda employees, which amounted to 71.9% while 28.1% of employee performance was influenced by other variables. Partially leadership, knowledge, skills and motivation have a significant effect on the performance of Bappeda employees. Motivational variables have a dominant influence on the performance of employees of Bappeda in Bojonegoro Regency. Keywords: leadership, knowledge, skills, motivation, performance